Double take : a memoir - Connolly, Kevin Michael, 1985- (HarperStudio, 2010)
A memoir in which photographer, skier, and skateboarder Kevin Connolly tells what it was like to grow up without legs, discussing his loving parents, his dad's continuing efforts to invent devices to make his life easier, his participation in sports, and his habit of taking pictures of people who stare at him--a project that became a traveling exhibit.